What killed Chervyakov? Traditional Culture in A.P. Chekhov’s Story “Death of a Government Clerk” (Proceedings of Southern Federal University. Philology, 2019)
Marina Ch. Larionova, Olga A. Shepeleva (Rostov-on-Don, Russian Fеderation. Donetsk, DNR)A.P. Chekhov chooses character’s sneezing as a starting point of the story “Death of a government clerk”. In traditional culture sneezing owns set of stable connotations. A.P. Chekhov, who was born and lived for a long period of time in Taganrog, was well acquainted with traditional culture in its urban and province recension. The writer also studied works on folk medicine, ethnography and folklore. Various superstitions and omens are connected with sneezing. A.P. Chekhov brings sneezing into correlation with human’s social being, so it becomes character’s social function as it later results in Chervyakov’s death. Chervyakov is sick with respect for rank, i.e. social disease. A.P. Chekhov makes physiological state and social status isomorphous, so they equally reflect the character. However, Chervyakov’s sneezing in the story is not physical and social act only, but it is also metaphysical. In national perception concept of sneezing is connected with soul and death. Thus, connection between sneezing (minimal and independent from human action) and death (catastrophic event) becomes obvious and the result is inevitable. There is one more important character in the story – general. Between these two characters peculiar relationships of character’s doubling are set. Both of them are from the system which kills a human in a human-being. Chervyakov died because he “sneezed out” himself. Human is socially and physically lonely in this wrongly organized world. Traditional culture can become a kind of comment on Chekhov’s works, making details clear, helping to form famous Chekhov’s “underlying theme”.Key words: A.P. Chekhov, “Death of a government clerk”, sneezing, traditional culture.DOI 10.23683/1995-0640-2019-1-36-41